FACTORS INFLUENCING LOW ANTENATAL CARE VISITS AT THE PAMAR COMMUNITY HEALTH CENTER IN THE DISTRICT HEALTH CENTER RUSIP BETWEEN CENTRAL ACEH DISTRIC ACEH PROVINCE IN 2025 - Amira, Tasya; Herna Rinayani Manurung; Sonia Novita Sari; Safira Sarnima; Emiya Agustina Surbakti; Elestra Natalia Butar-butar; Rohhasianti Br Sagala, (Mitra Husada Health Internasional Conference (MIHHICo), 2025)
Background: The persistently high MMR and IMR in Indonesia necessitate robust intervention, specifically through mandated Antenatal Care (ANC) visits. In the Rusip Antara Subdistrict, particularly at the Pamar Public Health Center, there is a documented shortfall in first-trimester ANC participation. Objective: The study sought to investigate the variables behind this low attendance within the Central Aceh Regency in 2025.Methods: The investigation was designed as an analytical observational study with a cross-sectional framework. The researchers utilized a total sampling technique, involving 40 pregnant women who had completed their first trimester. Data gathered via structured questionnaires were processed through Chi-square analysis to determine variable relationships. Results: Statistical testing revealed that education, knowledge, and attitude significantly influenced ANC visits, while cultural influences remained statistically insignificant (p=0.744). Conclusion: Because education and attitude are primary predictors of healthcare seeking, the Pamar Public Health Center should prioritize targeted health education to enhance maternal engagement with prenatal services.